Regulation of Tumor Angiogenesis by the Immune System - Schadler Stewart, Keri; W. Ryeom, Sandra (Current Angiogenesis (Discontinued), 2012)
Tumor immune surveillance is the process by which the immune system recognizes and destroys tumor cells, without which cancer would be more frequent among humans. Tumor immune surveillance has long been known to consist of a direct tumor cell lysis component, dependent on the adaptive immune system. New evidence demonstrates that in addition to a direct effect on tumor cells, the immune system regulates tumor growth via regulation of angiogenesis. Many of the cell types of both the innate and adaptive immune system have either pro or anti-angiogenic functions. In this review, we discuss key data for the angiogenesis regulatory role of each of the major immune cell types.
Keywords: Severe Combined